2022
DOI: 10.3390/ijms231911013
|View full text |Cite
|
Sign up to set email alerts
|

The Autism Spectrum Disorder-Associated Bacterial Metabolite p-Cresol Derails the Neuroimmune Response of Microglial Cells Partially via Reduction of ADAM17 and ADAM10

Abstract: The bacterial metabolite 4-methylphenol (para-cresol or p-cresol) and its derivative p-cresyl sulfate (pCS) are elevated in the urine and feces of children with autism spectrum disorder (ASD). It has been shown that p-cresol administration induces social behavior deficits and repetitive behavior in mice. However, the mechanisms of p-cresol, specifically its metabolite pCS that can reach the brain, in ASD remain to be investigated. The pCS has been shown to inhibit LPS-stimulated inflammatory response. A Disint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…29,30 Derangements in amyloid processing may also be involved in ASD. [31][32][33][34] Interestingly, VPA has been found to inhibit g-secretase cleavage of amyloid precursor protein, reducing brain amyloid load and VPA hypocholesterolemic effects could be a mechanism contributing to its favorable impact on ASD via amyloid reduction. 35 This requires further exploration as most studies of this relationship have focused on cognitive impairment in older population and not on developmental effects on amyloid.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Derangements in amyloid processing may also be involved in ASD. [31][32][33][34] Interestingly, VPA has been found to inhibit g-secretase cleavage of amyloid precursor protein, reducing brain amyloid load and VPA hypocholesterolemic effects could be a mechanism contributing to its favorable impact on ASD via amyloid reduction. 35 This requires further exploration as most studies of this relationship have focused on cognitive impairment in older population and not on developmental effects on amyloid.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that p-cresol-producing bacteria may be present in the distal ileum. pCS is formed from p-cresol through its metabolism, which is absorption in the intestine [ 42 ]. It has been suggested that nearly 95% of p-cresol is metabolized in the body into pCS via O-sulphonation.…”
Section: Discussionmentioning
confidence: 99%
“…Two meta-analyses found comparable outcomes in children with ASD. Moreover, patients with ASD who have gastrointestinal issues may exhibit substantial behavioral manifestations such as anxiety, self-injury, and violence [ 32 , 33 , 34 ]. A growing body of research suggests that the gut microbiota is directly or indirectly linked to ASD symptoms, in part by impacting the immune system and metabolism [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%